생쥐에서 간문맥수혈에 의한 췌장도세포동종이식 후 이식생존율의 향상 - 박종권(Jong Kwon Park) (Annals of surgical treatment and research, 2007)
Purpose: Considering the complications of nonspecific immunosuppression, as well as the availability of insulin, heavy immunosuppressive treatment to pancreatic islet transplantation patients is not justified. Antigen administration via the portal vein has been demonstrated to induce immunosuppression, and may present a possible mechanism for the induction of tolerance. Using a mouse model, without any immunosuppressive treatment, the islet allograft survivals were compared between portal venous transfusion and portal venous saline injection groups. Methods: Six C57BL/6J mice were used as pancreatic islet donors per Balb/c recipient mouse. Islets were harvested by digestion of the pancreata with collagenase, with subsequent Ficoll density gradient separation. Recipient mice were divided into two groups: seven mice received a portal venous injection of 0.1 cc saline (PVS) and eight a portal venous transfusion of 0.1 cc donor blood (PVT). Islets were transplanted into the subcapsular space of the left kidney. Transplantation failure was determined if the transplanted mouse failed to show a blood glucose level less than 200 mg/dl at 24 hours after the transplantation; these mice were not included in the statistics. Rejection was determined when the normalized blood glucose level (＜200 mg/dl) returned to above 300 mg/dl. Results: The mean islet equivalent numbers (IEQ) of the seven PVS and eight PVT mice were 893±262 and 911±288, respectively. The islet allograft survival of the PVS group ranged between 1 to 9 days; whereas, that of the PVT group ranged between 6 to 16 days. The PVT group showed significantly higher islet allograft survival than the PVS group (P=0.0443). Conclusion: A portal venous transfusion prolonged the islet allograft survival. (J Korean Surg Soc 2007;72:433-437) KCI Citation Count: 0